Implementasi Pendidikan Agama Kristen Terhadap Pembentukan Moral Siswa - Sylvana Talangamin; Jiffry Kawung (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to describe and analyze the implementation of Christian Religious Education on the moral formation of students at SMP Negeri 4 Manado. In this study the authors used a qualitative approach. Data collection techniques through observation, interviews, and documentation. The results of the study stated that (1) The implementation of Christian Religious Education on the moral formation of students at SMP Negeri 4 Manado has been carried out through teaching and learning activities and mentoring but has not been maximized in the formation of student morals. (2) The implementation of the guidance carried out by the teacher is to direct students to get used to living according to Christian teachings, for example living honestly, politely in speech, polite in acting, helpful, not arrogant and able to keep themselves from associating freely. (3) Obstacles in implementing PAK to shape the morale of students at SMP Negeri 4 Manado, namely the learning conditions during this COVID-19 period which requires students to study from home with inadequate facilities, environmental factors that do not support living conditions, infrastructure facilities in schools that are not yet available. adequate and the role of parents who are less concerned when students study at home. (4) Efforts made by PAK teachers to shape students' morale are trying to find fun and creative learning methods, preparing learning strategies that are appropriate to the current situation and circumstances of COVID-19 and being an example in accordance with Christian teachings From the research results, it is recommended for PAK teachers and parents to be more active in implementing Christian Religious Education so that they can shape students' morale to be good.